ANALISA KEKUATAN FLANGE PADA SISTEM PEMIPAAN PRIMER REAKTOR TRIGA 2000 BANDUNG - Hendra Prihatnadi; Budi Santoso (BATAN, 2011)
In the primary cooling system installation TRIGA 2000 reactor, grafting piping system using flange connection for connecting or demolition if necessary. This connection includes a connection pipe to the fittings, valves, equipment, or other separate parts in the piping system. Analysis of flange force on the primary coolant piping system of the TRIGA 2000 reactor was performed with stress analysis software CAESAR II. The steps required in the analysis include data collection for model input, modeling, static analysis. Analysis of flange strength using the